SIMILE DALAM PUISI KITAB AL-HUBB KARYA NIZAR QABBANI (ANALISIS STILISTIKA). - ALI MUFTI; Mohamad Yusuf Ahmad Hasyim; Ahmad Miftahuddin (Lisanul Arab: Journal of Arabic Learning and Teaching, 2022)
Simile is similaring one to another because of a simlilarity in a few adjectives by using adat. Researcher prefers poem of Kitab Al-Hubb, authorized by Nizar Qabbani because there are many love expressions of him to his lovely person. Purposes of the research are to know what sentences those contain tasybih, rukun tasybih, types tasybih in poem of Kitab Al-Hubb, authorized by Nizar Qabbani. Type of the research is qualitative by research design of library research. Thus the data source based on poem of Kitab Al-Hubb, authorized by Nizar Qabbani. Data collecting is done by using technic of documentation. Instruments that used are data card and recapitulation sheet. Besides, the data analyze is done by using agih technic. The result points that the total of at-tasybihs in poem of Kitab Al-Hubb, authorized by Nizar Qabbani is 39 datas. Then, those 39 datas are analyzed on the type of tarf tasybih based on hissi and aqli, Based on mufrod and murokkab, Based on its total, two tarf tasybihs. Then, 39 datas are analyzed into type of tasybih based on those contain 21 wajhu syibhi or not, the 21 datas are made of 18 data tasybih mujmals and 3 data tasybih mufashals. Based on there is adat tasybih or not, there are 21 datas that all of them are include on type of tasybih mursal. Based on there are adat tasybih and wajhu syibh or not, there are 18 datas those called by tasybih baligh then.